Revision history of "Three-term recurrence for Bateman F"

Jump to: navigation, search

Diff selection: Mark the radio boxes of the revisions to compare and hit enter or the button at the bottom.
Legend: (cur) = difference with latest revision, (prev) = difference with preceding revision, m = minor edit.

  • (cur | prev) 03:06, 22 June 2016Tom (talk | contribs). . (334 bytes) (+334). . (Created page with "==Theorem== The following formula holds: $$n^2 F_n(z) = -(2n-1)z F_{n-1}(z)+(n-1)^2 F_{n-2}(z),$$ where $F_n$ denotes the Bateman F. ==Proof== ==References== * {{BookRef...")